THE FINDING PROBLEM FOR A NON-HOMOGENEOUS EQUATION WITH A MIXED-TYPE PRIVATE PRODUCT WITH TWO GENERATION LINES - Sharipov J. I. (Web of Journals Publishing, 2024)
This work considers the boundary value problem for a heterogeneous mixed-type partial differential equation with two degeneracy lines, obtains a representation of the solution, obtains an a priori estimate of the solution, and obtains theorems proving the uniqueness and conditional stability of the solution in the set of correctness.
Keywords: incorrect problem, mixed type, a priori estimate, set of correctness, uniqueness, conditional stability.